Analysis of Cascara Business Competition Using Porter’s Five Forces Model at PT Agritama Sinergi Inovasi - Gika, Eline Nuha Nurrohmah; Purwaamijaya, Btari Mariska; Maesaroh, Syti Sarah (LPPM Universitas Trunojoyo Madura, 2024)
The cascara market in Indonesia has great potential due to the increasing interest in health-oriented beverages. However, PT Agritama Sinergi Inovasi (AGAVI) faces competitive challenges in the form of high supplier bargaining power, lack of awareness of the domestic market, and threats from substitute products such as tisane and herbal tea. This study aims to analyze the level of competition in the cascara business of PT Agritama Sinergi Inovasi (AGAVI) using Porter's Five Forces model. The research method used is a qualitative approach through interviews, observations, and documentation to collect data. Data analysis was carried out descriptively with source triangulation to ensure the validity of the findings. The results of the analysis show that the bargaining power of suppliers is at a high level, while the bargaining power of buyers and the threat of newcomers are at a medium level. The threat of substitute products is at a low level, while the level of competition between competitors is at a medium level, providing innovation opportunities for AGAVI. This research contributes to enriching the understanding of business competition in the health-based beverage market, especially in the sustainability-based beverage industry. These findings provide insights for AGAVI to improve competitiveness by expanding markets, especially for customer loyalty in the B2C segment, market education, and strengthening partnerships with local coffee farmers, while creating additional income opportunities for coffee farmers and supporting industry sustainability.